A prospective study of fetomaternal outcomes in patients with eclampsia in a tertiary care hospital in Jharkhand - Priyanka; Atima Bharti (New Indian Journal of OBGYN)
Objectives: To determine fetomaternal outcomes in patients with eclampsia. Methods: This prospective observational cohort study was conducted at Rajendra Institute of Medical Sciences, Ranchi, Department of Obstetrics and Gynaecology from April 2019 to September 2020. 200 patients who came with presence of seizures or coma (eclampsia) which could not be attributed to other causes and admitted in the emergency (labour room) were included in the study. The fetomaternal outcomes were determined among all the enrolled patients in terms of mortality, mode of delivery and baby weight. Results: The mean age of the patients were 22.7 years with 69.5% primi and 21.5% multigravida. Antepartum eclampsia was present in 90% cases and postpartum eclampsia was present in 10% cases. Induction for labour was done in 53.30% patients, with cerviprime gel being the most common method. LSCS were performed in 30.27% cases and instrumental delivery in 4.86%; most common indication of LSCS was fetal distress. Preterm occurred in 42 (25.76%) patients. Maternal death occurred in 37 (18.50%) patients; most common cause being acute pulmonary edema followed by disseminated intravascular coagulation (DIC). Neonatal death occurred in 17(10.83%) babies for which birth asphyxia and prematurity were the common causes. Conclusion: The findings of the study revealed that eclampsia is significant obstetric emergency which results in significant maternal as well as fetal morbidity and mortality. The knowledge, screening and proper management may help in the result of a better outcome in such patients.